Pengaruh Modal, Tenaga Kerja, dan Bahan Baku terhadap Pendapatan Industri Mebel Kayu di Kota Banjarmasin (Studi Kasus Kelurahan Alalak Tengah Kecamatan Banjarmasin Utara) - Pertiwi, Ayu (PPJP ULM, 2018)
The purposes of this research are (1) To understand the effect of production, landarea, and human resources to the development of the agriculture sub-sector in TanahBumbu District; (2) Which sub-sector is the most important to the development of theagriculture sub-sector in Tanah Bumbu District. The object of this research is three sub-sectors in Tanah Bumbu District(agriculture, forestry, and fishery). The method of this research is a regression analysis of panel data with the Common Effect model. The result of this research that production, land area, and human resourcesboth individually (partial) and together have a positive effect and significant to the development of the agriculture sub-sector in Tanah Bumbu District. The forestry sub- sector gives the most positive contribution to the development of the agriculture sub-sector in Tanah Bumbu District.